Importance of weed endemic in subsistence agriculture in Ladakh region and their traditional management - Raghuvanshi, M. S.; Tewari, J. C.; Bhatt, R. K.; Landol, Stanzin; Spalbar, Enoch; Dorje, Ngawang; Raza, Mohd. (Indian Farming, 2018)
Subsistence agriculture in Ladakh region requires a thorough understanding of its physical, economical and social realities beforerecommendation of any weed management technologies in theregion. There is a need to make farming community aware of theweed menace and its impact on crop yields. Weeds in the region are used as fodder for animals, also for various medicinal purposes. Cultural methods of weed management like use of higher seed rate, weeding tools, mulching etc., may be accepted by the farmers of the region.